Lembaga perkreditan desa sebagai penopang keajegan budaya ekonomi masyarakat Bali - Anak Agung Ngurah Gede Sadiartha (Pusat Kajian Bali Universitas Udayana, 2017)
Village Credit Union “Lembaga Perkreditan Desa” (LPD) continues to develop into an autonomous and tough intermediary institution. This paper discusses LPD as a model of superior traditional financial institutions, and its role in supporting the economic culture of the people of Bali. This paper is the result of qualitative research with data obtained from observation, documentation study and interview with 10 informants: LPD credit recipients, practitioners and observers of LPD. The data were descriptively, qualitatively, and interpretatively analyzed using economic management theory and the theory of social practice (Bourdieu). The results show: Firstly, LPD develops into a formidable traditional financial institution because: (a) LPD was autonomous, not subject to central policy, but refer to local regulations and awig-awig; (b) Implementation of modern global banking management, ie management functions, 5C principles, and innovation of LPD products and implementastion of cultural values ??of local organizations including Hindu philosophy on prosperity Tri Hita Karana, Catur Asrama and human relations manyamebraya. Secondly, the existence of LPD was able to improve socio-economic welfare and sustain the cultural traditions of indigenous villagers in Bali.